(untitled) (International Journal of Pharmaceutical and Life Sciences, 2012)
To develop a novel dosage form of ibuprofen loaded solid dispersion with improved dissolution, formulations were developed using mixture of tween 80 & span 80 with a sugar such as dextrose, icing sugar. Percentage of tween 80 & span 80 was 10% & 5%, 7.5% & 7.5%, 5% & 10% and amount of sugar was fixed (1.2 g). In-vitro dissolution study was conducted in phosphate buffer (pH 7.2) for 1 hour. Release property from formulations of both sugars was investigated. In both cases, enhanced release property was observed where the release was compared with pure ibuprofen powder. Formulations having same amount of tween 80 & span 80 showed maximum release of drug. Formulations of icing sugar showed maximum release of drug within 1 hour time frame than the formulations of dextrose. DOI: http://dx.doi.org/10.3329/ijpls.v1i1.12946 International Journal of Pharmaceutical and Life Sciences Vol.1(1) 2012